All-trans retinoic acid in non-promyelocytic acute myeloid leukemia: driver lesion dependent effects on leukemic stem cells. Issue 20 (17th October 2020) - Nguyen, Chi H.; Grandits, Alexander M.; Purton, Louise E.; Sill, Heinz; Wieser, Rotraud
ABSTRACT: Acute myeloid leukemia (AML) is an aggressive, often fatal hematopoietic malignancy. All-trans retinoic acid (atRA), one of the first molecularly targeted drugs in oncology, has greatly improved the outcome of a subtype of AML, acute promyelocytic leukemia (APL). In contrast, atRA has so far provided little therapeutic benefit in the much larger group of patients with non-APL AML. Attempts to identify genetically or molecularly defined subgroups of patients that may respond to atRA have not yielded consistent results. Since AML is a stem cell-driven disease, understanding the effectiveness of atRA may require an appreciation of its impact on AML stem cells. Recent studies reported that atRA decreased stemness of AML with an FLT3 -ITD mutation, yet increased it in AML1-ETO driven or EVI1 -overexpressing AML. This review summarizes the role of atRA in normal hematopoiesis and in AML, focusing on its impact on AML stem cells.